The Association Between Qtc, Qtd, TPE, And Fragmented QRS Before And After PPCI With Hospital Mortality In STEMI Patients - Namazi, Mohammad H.; Salehi, Ayoub; Akbarzadeh, Mohammad Ali; Parsa, Saeed Alipour; Safi, Morteza; Vakili, Hossein; Saadat, Habibollah; Eslami, Vahid; Kiaee, Farshid Heidarpour; Nourian, Saeed; Sohrabifar, Nasim; Khaheshi, Isa (Cardiovascular & Haematological Disorders - Drug Targets, 2022)
Background: ST-elevation myocardial infarction (STEMI) is known to be associated with significant arrhythmia and consequent mortality. QT prolongation is a risk factor for arrhythmia in STEMI patients who underwent primary percutaneous coronary intervention (PPCI). The aim of this investigation was to evaluate the association of corrected QT interval (QTc), QT dispersion (QTd), T-wave peak to end (TPE), and fragmented QRS with mortality in these patients. Methods: Eligible patients with the characteristic symptoms of STEMI who underwent PPCI were included. QTc, QTd, TPE, and fragmented QRS were measured before and after the PPCI. These predictors were compared between patients who died during hospitalization and discharged patients. Results: After coronary angiography, 10 patients (4%) died during the hospitalization after PPCI. Comparing the non-survivers and discharged patients in terms of arrhythmia predictors showed that the mean QT dispersion and TPE before intervention were significantly higher in the non-survivors. Also, the number of patients who experienced fragmented QRS before and after the intervention was significantly higher in the non-survivors. Conclusion: These data suggested that evaluating such arrhythmia predictors, especially before PPCI, could be used as a predictor of mortality in STEMI patients who underwent PPCI.
Keywords: PPCI